Christian Morality and Social Inequality: A Contextual Study of the Crisis of Public Trust in People's Representatives - Sanjaya, Yusak; Santosa, Rivosa (Asian Journal of Philosophy and Religion, 2025)
The purpose of this contextual theology-based study is to analyze the leadership character transformation embedded in Christian ethical values, particularly in preventing corruption, upholding justice, and building institutional trust. Through a qualitative study with philosophical textual analysis and selected case studies, this study reveals that persistent social inequality is often maintained by a system that exploits political power legitimation. Meanwhile, religious institutions, particularly churches, which play a crucial role in shaping the character of leaders with faith-based integrity, are still struggling with both internal and external challenges. The findings of this study showed that leadership transformation based on Christian morality should not merely focus on individual transformation but also systemic, which requires a reconciliation between Gospel values and contemporary democratic practices.